2008
DOI: 10.1128/ec.00215-07
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of C/D snoRNA in rRNA Processing and Modification inTrypanosoma brucei

Abstract: Most eukaryotic C/D small nucleolar RNAs (snoRNAs) guide 2-O methylation (Nm) on rRNA and are also involved in rRNA processing. The four core proteins that bind C/D snoRNA in Trypanosoma brucei are fibrillarin (NOP1), NOP56, NOP58, and SNU13. Silencing of NOP1 by RNA interference identified rRNAprocessing and modification defects that caused lethality. Systematic mapping of 2-O-methyls on rRNA revealed the existence of hypermethylation at certain positions of the rRNA in the bloodstream form of the parasites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
86
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 71 publications
6
86
0
Order By: Relevance
“…However, snoRNAs Cl2 and Cl3 exhibited greater target methylation as compared to Cl1 (Barth et al 2008). These results showed that other factors aside from copy number and expression level were influencing the modification guiding process, such as the presence of secondary structure at the modification site.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, snoRNAs Cl2 and Cl3 exhibited greater target methylation as compared to Cl1 (Barth et al 2008). These results showed that other factors aside from copy number and expression level were influencing the modification guiding process, such as the presence of secondary structure at the modification site.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported recently that position U611 within the LSU is 66.2% hypermethylated in bloodstream versus procyclic forms; this may help the parasite to adapt to a higher vertebrate host temperature (Barth et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These ribosomal modifications are crucial for protein synthesis and fidelity and govern the sensitivity to ribosome-based antibiotics. [2][3][4][5][6][7] In most eukaryotes, the pseudouridylation guide snoRNAs consist of two hairpins, a 5' hairpin followed by a single-stranded H-box (ANANNA, where N stands for any nucleotide) and a 3' hairpin followed by an ACA-box. The snoRNA's pseudouridylation pocket consists of two short sequences that are complementary to the flanking rRNA sequence of the uridine to be converted.…”
mentioning
confidence: 99%